Detection of oxidized and glycated proteins in clinical samples using mass spectrometry — A user's perspective - Thornalley, Paul J.; Rabbani, Naila (Biochimica et biophysica acta, 2014)
Proteins in human tissues and body fluids continually undergo spontaneous oxidation and glycation reactions forming low levels of oxidation and glycation adduct residues. Proteolysis of oxidised and glycated proteins releases oxidised and glycated amino acids which, if they cannot be repaired, are excreted in urine. In this review we give a brief background to the classification, formation and processing of oxidised and glycated proteins in the clinical setting. We then describe the application of stable isotopic dilution analysis liquid chromatography-tandem mass spectrometry (LC-MS/MS) for measurement of oxidative and glycation damage to proteins in clinical studies, sources of error in pre-analytic processing, corroboration with other techniques – including how this may be improved – and a systems approach to protein damage analysis for improved surety of analyte estimations. Stable isotopic dilution analysis LC-MS/MS provides a robust reference method for measurement of protein oxidation and glycation adducts. Optimised pre-analytic processing of samples and LC-MS/MS analysis procedures are required to achieve this. Quantitative measurement of protein oxidation and glycation adducts provides information on level of exposure to potentially damaging protein modifications, protein inactivation in ageing and disease, metabolic control, protein turnover, renal function and other aspects of body function. Reliable and clinically assessable analysis is required for translation of measurement to clinical diagnostic use. Stable isotopic dilution analysis LC-MS/MS provides a “gold standard” approach and reference methodology to which other higher throughput methods such as immunoassay and indirect methods are preferably corroborated by researchers and those commercialising diagnostic kits and reagents. This article is part of a Special Issue entitled Current methods to study reactive oxygen species - pros and cons and biophysics of membrane proteins. Guest Editor: Christine Winterbourn. •Proteins of tissue and body fluids have low level oxidation and glycation adducts.•Cellular proteolysis releases glycated and oxidized amino acids which are then excreted.•Robust adduct measurement is made by stable isotopic dilution analysis LC-MS/MS.•Adduct levels relate to protein turnover, health status, renal function and aging.•A systems biology modelling approach to protein oxidation and glycation is given.